Land use changes alter microbial functional gene diversity and its relationship with soil ecosystem multifunctionality in a subtropical estuary - Liu, Zi-Kai; Zhang, Lige; Jin, Shengsheng; Yu, Hanxia; He, Ji-Zheng; Shen, Ju-Pei (Frontiers in Microbiology, 2025)
Land use change in coastal wetlands is often associated with microbial diversity and function, which plays a crucial role in mediating soil ecosystem multifunctionality (EMF). However, the linkage between microbial functional genes and soil EMF under different land uses requires further investigation. This study investigated the relative abundance and community structure of microbial functional genes associated with carbon (C), nitrogen (N), phosphorus (P) and sulfur (S) cycling and their relationship with soil EMF across five different land uses (reed wetland, tidal flat, grassland, agricultural land and fallow land) in the Min River Estuary using high-throughput quantitative PCR technique. Results showed that microbial functional gene composition changed significantly across different land uses. Soil electrical conductivity (EC) ranged from 5.73 mS/cm (tidal flat) to 0.29 mS/cm (fallow land), driving significant shifts in microbial functional gene composition. Soil EMF exhibited a U-shaped trend across reed wetlands, tidal flats, grasslands, agricultural lands, and fallow lands, with the lowest in grasslands and peaking in fallow lands. Random forest analysis indicated that soil EC as the most influential environmental factor shaping microbial functional gene compositions, while functional gene richness directly correlated with EMF. Notably, soil EC modulates the relationship between microbial functional gene compositions and EMF. These findings enhance our understanding of soil EMF variations across different coastal land uses and underscore the need to integrate microbial functionality into coastal wetland management.